2014
DOI: 10.5812/thrita.17989
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Physician Directories in Tehran Considering the Present Situation and Improvement Suggestions

Abstract: Background: Physician directories are among the most important databases in health systems. Objectives: The aim of this study was to estimate the accuracy of physician directories in Tehran, Iran. Materials and Methods: This was a cross-sectional study. Tehran, the capital of Iran, was selected for study. Specialists', fellowships' and subspecialists' information were extracted from Islamic Republic of Iran Medical Council (IRIMC) website and completed using the White Book. The data were gathered through telep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…10 Bed occupancy rate (BOR) and average length of stay (ALS) are key indicators of hospital performance. [12][13][14][15][16] The average BOR of SSO hospitals is reported to be 76.1%, 11 close to that of OECD countries (77%), Belgium (78%) and France (75%), higher than that of the United States (65%,) and lower than that of Norway and Canada (90%) and the United Kingdom (85%), as reported in 2013. 13 On the other hands, the ALS in SSO hospitals is reported to be 2.7 days which is extremely lower than that of the OECD countries (8.1 days) 11 and even below the minimum standard of 3.5 days required by the MOHME.…”
Section: Evaluation Of the Effect Of Additive Metformin To Progesteromentioning
confidence: 99%
“…10 Bed occupancy rate (BOR) and average length of stay (ALS) are key indicators of hospital performance. [12][13][14][15][16] The average BOR of SSO hospitals is reported to be 76.1%, 11 close to that of OECD countries (77%), Belgium (78%) and France (75%), higher than that of the United States (65%,) and lower than that of Norway and Canada (90%) and the United Kingdom (85%), as reported in 2013. 13 On the other hands, the ALS in SSO hospitals is reported to be 2.7 days which is extremely lower than that of the OECD countries (8.1 days) 11 and even below the minimum standard of 3.5 days required by the MOHME.…”
Section: Evaluation Of the Effect Of Additive Metformin To Progesteromentioning
confidence: 99%
“…But after several inquiries it was found that this two sampling frames are out-of-date. As well, a study about accuracy of Iranian physician directories report their accuracy less than 60% [ 16 ]. Therefore, physician directories were assumed unreliable.…”
Section: Methodsmentioning
confidence: 99%
“…But after several inquiries it was found that this two sampling frames are out-of-date. As well, a study about accuracy of Iranian physician directories report their accuracy less than 60% (17). Therefore, physician directories were assumed unreliable.…”
Section: Study Samplingmentioning
confidence: 99%